Strangers in Time - Baldacci, David (New York : Grand Central Large Print, 2025)
"In London in 1944, a recently bereaved bookshop owner and two teenagers scarred by the Second World War come together, finding healing and hope in one another"--
large print
Keywords: Orphans -- Great Britain -- Fiction; Teenagers -- Fiction; World War, 1939-1945 -- Fiction; London (England) -- Fiction; Historical fiction; Large print books